The influence of current mood state, number of previous affective episodes and predominant polarity on insight in bipolar disorder. (2nd October 2017) - de Assis da Silva, Rafael; Mograbi, Daniel C.; Camelo, Evelyn Vieira Miranda; Peixoto, Ursula; Santana, Cristina Maria Teixeira; Landeira-Fernandez, Jesus; Morris, Robin G.; Cheniaux, Elie
Abstract: Background: Although many studies have explored the effect of current affective episodes on insight into bipolar disorder, the potential interaction between current mood state and previous affective episodes has not been consistently investigated. Objective: To explore the influence of dominant polarity, number of previous affective episodes and current affective state on insight in bipolar disorder patients in euthymia or mania. Methods: A total of 101 patients with bipolar disorder were recruited for the study, including 58 patients in euthymia (30 with no defined predominant polarity and 28 with manic predominant polarity) and 43 in mania (26 with no defined predominant polarity and 17 with manic predominant polarity). Patients underwent a clinical assessment and insight was evaluated through the Insight Scale for Affective Disorders. Results: Bipolar disorder patients in mania had worse insight than those in euthymia, with no effect of dominant polarity. In addition, positive psychotic symptoms showed a significant effect on insight and its inclusion as a covariate eliminated differences related to mood state. Finally, the number of previous manic or depressive episodes did not correlate with insight level. Conclusions: Mania is a predictor of loss of insight into bipolar disorder. However, it is possible that its contribution is linked to the more frequent presence of psychotic symptoms in this state. Dominant polarity and number/type of previous affective episodes have a limited impact on insight.